The sulfide precipitation behaviour of Cu and Au from their aqueous alkaline glycinate and cyanide complexes - Deng, Zixian; Oraby, Elsayed; Eksteen, Jacques (ELSEVIER SCIENCE BV, 2019)
© 2019 Elsevier B.V. Recently, a novel leach process for treating gold-copper ores and concentrates by glycine in the presence of starved cyanide in solutions were investigated where the Cu species are present as cuprous cyanide and cupric glycinate. Often Cu-levels in these gold ores are insufficient to economically justify solvent extraction with electrowinning, and sulfide precipitation is often preferred. This research reports the precipitation behaviour of Cu and Au from glycine-cyanide solutions by adding NaHS. Contrary to conventional cyanide-only systems, where all the copper is present as cuprous cyanide and alkaline precipitation of copper by sulfide addition is not feasible, the synergistic lixiviant system leads to a cupric-dominant system where copper can be precipitated. As the leach solution mainly contains glycine(Gly), cyanide(CN−) and copper in alkaline environment, the effect of glycine concentration [Gly], [HS−]: [CuT] and [CN−]: [CuT] molar concentration ratios, pH, temperature and reaction time on the Cu and Au precipitation have been studied, where [CuT] = [Cu+] + [Cu2+]. The results show that CuS precipitation (covelite) increased slightly with moderately elevated temperature, but decreased significantly with increasing [CN−]:[CuT] molar ratio. CuS precipitation was found to be insensitive to [HS−]:[CuT] molar ratio, glycine concentrations, pH and reaction time. Pre-oxidation of cuprous Cu+ to cupric Cu2+ was carried out using H2O2 to confirm the effect of oxidation state on copper precipitation. The kinetics of pre-oxidation was fast and above 95% of Cu+ were oxidized to Cu2+ in 5 min. The optimal [H2O2]:[Cu+] molar ratio was found to be 5:1 and 4:1 at [CN−]:[CuT] molar ratio of 2:1 and 1:1 respectively, implying significant reagent consumption to complete the reaction. With pre-oxidation and oxygen removal by nitrogen gas stripping, a Cu recovery as high as 96.5% was achieved with the addition of 1.4 mol of sulfide per mole CuT for 5 min at [Cu]:[CN−]:[Gly] molar ratio of 1:2:3 and pH 10.5. No Au co-precipitation was observed after precipitation for most of tested conditions. This study showed that a high level of Cu and Au separation can be obtained by sulphide precipitation with H2O2 pre-oxidation from CN-starved glycine solutions and allowing Au to be subsequently removed by activated carbon.